Islamisasi Ilmu Dan Relevansi Sains-Agama Dalam Al-Qur’an Dan Hadis - Majid, Abd (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2018)
In the midst of Western science and technology hegemony over the societies of countries around the world, especially Muslims, has had an enormous influence on the style, style and worldview of society, and the most striking is the secularization of science, technology and religion. There is a paradigm that considers the dividing wall between science and religion (Islam). This has led to the impression that religious education runs without the support of science and technology, in contrast, public education is present without a religious touch. To overcome the situation, one of the things to do is to open and re-understand the text of the Qur'an and Hadith, and to establish a dialectic between science, technology, and the science of religion. In addition, the